THE INFLUENCE OF CPR MEASURES TRAINING TOWARD KNOWLEDGE AND MOTIVATION TO HELP THE VICTIM OF CARDIAC ARREST IN HIGH SCHOOL STUDENT OF DARUL HIJRAH PUTERA ISLAMIC BOARDING SCHOOL - Ahmad Lathif; Abdurahman Wahid; Ifa Hafifah (Journal of Nursing Science Update (JNSU), 2018)
Cardiac arrest is the biggest dead cause in Europe. In Indonesia, it is estimated there are 10.000 cases of people who has cardiac arrest every year. However cardiac arrest can be handled with cardiac pulmonary resuscitation (CPR). In Darul Hijrah Putera Islamic Bording School, CPR has not been ever conducted. The method of this research used pre experimental with pre-post test design approach. The technique of collecting the data was by using probability sampling with simple random sampling approach. The samples were 40 respondents. The instrument used knowledge and motivation questioner to obtain respondentsâ€™ data on 21st December 2017 in Darul Hijrah Putera Islamic Boarding School. The Result in this research was obtained (p-value 0,000<Î±=0,05) on CPR action knowledge of the student and it was obtained (p-value= 0,000<Î±=0,05) on the studentsâ€™ motivation result. It explains that giving training about RJP to the students affect the knowledge and help the victim of cardiac arrest in student high school in Darul Hijrah Putera Islamic Boarding School. Â